KAZAKH CULTURE AS A PART OF WORLD CIVILIZATION - A, Uzakbaeva S.; K, Abildina S.; M, Rysbekova R.; E, Abeltayeva J.; Arman, erikhanova (International Journal of Psychosocial Rehabilitation, 2020)
Kazakh culture is a complex organizational structure with “organizational plasticity”, the flexible nature of the connections of its complexes, the simplicity and speed of the regrouping of elements. These qualities indicate a high level of organizational system of nomads. Now, as never before, the priority is the research of Kazakh culture with all responsibility and meticulousness. There is a need to establish the status of Kazakh culture and find its place in the hierarchy of world cultures. This is necessary, first of all, to increase the self-awareness of the Kazakh people, to strengthen their position and sovereignty.